The Relationship Between Patients' Knowledge, Attitude, and Actions With The Utilization of Dental and Oral Health Services at RSUD Taman Husada Bontang - Salsabila, Salma Nadya; Listiyawati; Sawitri, Endang (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: The issue of dental and oral health has been recognized as a significant health concern in Indonesia. Based on the 2018 Riskesdas report, the proportion of oral health problems in the community in Bontang was 57.26% while only 20.51% received treatment from dental medical personnel. The purpose of this study was to determine the relationship between knowledge, attitudes, and patient actions with the utilization of oral health services at RSUD Taman Husada Bontang. Material and Methods: This study used purposive sampling technique with a cross-sectional study design. In this study there were 96 respondents selected as samples who were utilizing oral health services at the Dental Polyclinic of RSUD Taman Husada Bontang. This study used a questionnaire to measure patient behavior in utilizing oral health services. Results and Discussions: The results showed that patient knowledge and attitudes (99%) were in the good category, patient actions (94.8%) were in the good category, and oral health service utilization (97.9%) was in the good category. The results of the chi-square test on knowledge and attitudes with the utilization of oral health services showed p = 0.000 (p < 0.05), and the chi-square test on the action category with the utilization of oral health services showed p = 0.004 (p < 0.05). Conclusion: The results showed a relationship between knowledge, attitudes, and patient actions with the utilization of oral health services at RSUD Taman Husada Bontang.